Desvendando o trânsito : uma sequência didática inspirada na metodologia de episódios de modelagem para o ensino de cinemática no ensino fundamental - Mello, Maria Aparecida Maia de (2020)
Physics teaching at school still presents a distant approach to the students' reality. Nowadays establishing a connection between theory and reality in the science curriculum component in the 9th grade is a challenge for teachers, mainly due to the small number of educational productions aimed at the introduction to Physics in the Final Years of Elementary School. Thus, this dissertation aims to approach Physics applied to traffic as a didactic proposal, starting from the students' social context, to investigate the possibility of creating better conditions for meaningful learning, in the sense of Ausubel, in relation to the concepts of referential, movement, rest, time, position, displacement, speed and acceleration. For this, we carried out a pedagogical intervention, in the sense of Damiani, consisting of a didactic sequence entitled “Unveiling the traffic”. For the construction of such a sequence, the model proposed by Zabala and Heidemann's modeling episodes methodology were taken into account. The sequence was divided into seven didactic modules and an evaluation seminar distributed in the stages of initial discussion, investigation and final discussion. Finally, we evaluated the potential of the didactic sequence in the teaching of physics applied to traffic to promote the students' meaningful learning. According to the results found, we can consider that the didactic sequence reached the objectives foreseen in the didactic modules and showed signs of occurrence of significant learning. As an educational production generated from this research, the didactic sequence was constructed in order to serve as a didactic tool for teachers of basic education. In discussing the results, the students demonstrated that the students were able to look critically at the socioenvironmental aspects that are intrinsically interconnected with the possible causes of accidents on the highway. Furthermore, we realized that the class managed to analyze that a small difference above the permitted speed is already enough to cause serious accidents.